2017
DOI: 10.4103/ijt.ijt_48_16
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of nutritional deficiencies in hair loss among Indian participants: Results of a cross-sectional study

Abstract: Background:Nutritional deficiencies are known to be associated with hair loss; however, the exact prevalence is not known.Aims:The aim of this study is to evaluate the prevalence of nutritional deficiencies in participants with hair loss.Materials and Methods:In this cross-sectional study, 100 enrolled participants were divided into telogen effluvium (TE), male-pattern hair loss (MPHL), and female-pattern hair loss (FPHL) based on the type of hair loss. All participants underwent laboratory estimation for micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
21
1
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 11 publications
3
21
1
4
Order By: Relevance
“…However, in previous studies, patients with alopecia had various amino acid deficiencies. In particular, histidine deficiencies among essential amino acids and alanine deficiencies among nonessential amino acids were found in over 90% of male pattern baldness patients [18]. Additionally, in our previous study, we confirmed that polyamines synthesized through arginine to agmatine are associated with pattern baldness in human hair samples [19,20].…”
Section: Discussionsupporting
confidence: 79%
“…However, in previous studies, patients with alopecia had various amino acid deficiencies. In particular, histidine deficiencies among essential amino acids and alanine deficiencies among nonessential amino acids were found in over 90% of male pattern baldness patients [18]. Additionally, in our previous study, we confirmed that polyamines synthesized through arginine to agmatine are associated with pattern baldness in human hair samples [19,20].…”
Section: Discussionsupporting
confidence: 79%
“…In contrast to the study of Gowda et al [ 109 ], a study conducted by Deo et al in India aimed to detect the prevalence of several forms of hair loss in females and to correlate these data with levels of hemoglobin and serum ferritin. This observational study involved 135 subjects, the majority (62.2%) of whom had TE, with the next largest group having FPHL (23.7%).…”
Section: Ironmentioning
confidence: 99%
“…Their results indicate that a relatively higher proportion of participants with TE (20.37%) had iron deficiency compared to those with FPHL (16.67%) and male pattern hair loss (MPHL) (2.94%) ( p = 0.069). Furthermore, transferrin saturation and ferritin levels were lower in patients with FPHL (41.67%) and TE (40.74%) than in patients with MPHL (11.76%) [ 109 ]. Iron deficiencies were found to be related to gender rather than to type of hair loss.…”
Section: Ironmentioning
confidence: 99%
“…Similarly, the role of vitamin D has been much discussed in several pathologies, including TE; a study involving 80 women with TE demonstrated significantly lower levels in relation to the control group, although the mechanism of action has not yet been established. 21 …”
Section: Discussionmentioning
confidence: 99%